Multicomponent exercise program effects on fitness and cognitive function of elderlies with mild cognitive impairment: Involvement of oxidative stress and BDNF - Rondão, Catarina Alexandra de Melo; Mota, Maria Paula; Oliveira, Maria Manuel; Peixoto, Francisco; Esteves, Dulce (Frontiers in Aging Neuroscience, 2022)
Regular exercise has been shown to be one of the most important lifestyle influences on improving functional performance, and decreasing morbidity and all-cause mortality among older people. However, although there is some evidence on the effects of aerobic training on oxidative stress, there is little information regarding the effects of multicomponent exercise (dual-task training) and combination of exercise with cognitive stimulation on oxidative stress. In this context, the aim of this study was to verify the effects of a multicomponent exercise program on physical fitness and cognitive function in the elderly with mild cognitive impairment and determine the role of oxidative stress and brain-derived neurotrophic factor (BDNF). At baseline, 37 elderly nursing home residents with mild cognitive impairment were divided into two groups: the control group (CG, n = 12, 81.8 years) and the experimental group (EG, n = 25, 83.2 years). These elderlies followed multicomponent exercise training for 24 weeks, with two sessions per week and 45–50 min per session. The exercises included both aerobic and strength exercises, considering functional movements and light to moderate intensity. Cognitive stimulation comprehended exercises based on word games, puzzles, mathematical calculations, forward and backward counting, computer exercises, exergames, and games on a balanced platform. Physical assessments (weight, height, and body mass index), health and functional parameters (fitness tests: chair stand, arm curls, chair sit-and-reach, eight feet up-and-go, back scratch, 6-min walking, feet together, semi-tandem, and full tandem), lipid profile (total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglycerides), measures of lipid peroxidation damage, thiobarbituric acid reactive substances (TBARS), total antioxidant capacity (TAC), and BDNF were measured in plasma, based on which analyses were performed before and after the 24 weeks of the multicomponent exercise intervention. The results showed an overall improvement in physical and functional performance. Regarding biochemical measures, multicomponent exercises lead to a significant decrease in oxidative damage. The results indicate that multicomponent exercise training induces benefits in functional capacity and reduces damage due to oxidative stress.